CORE STABILITY EXERCISE LEBIH BAIK DIBANDINGKAN BACK STRENGTHENING EXERCISE DALAM MENINGKATKAN AKTIVITAS FUNGSIONAL PADA PENGRAJIN BATIK CAP DENGAN KELUHAN LOW BACK PAIN DI KABUPATEN PEKALONGAN - ade irma Nahdliyyah; N Adiputra; Sugijanto - (Sport and Fitness Journal, 2015)
Preservation batik has become cultural heritage of Indonesia also needs to be balanced with the protection of the health of batik craftsmen. The health condition of batik craftsman is one off factor in the sustainability of batik in Indonesian because the capital of craftsman working productivity. Workloads such as position and wrong posture at works can lead to complaints of the musculoskeletal system. One of them is low back pain (LBP). LBP can reduce the functional abilities of the craftsmen. LBP is a very common problem in people working age. Structured exercise an option for the treatment of low back pain. Exercise to reduce pain and improve functional activities. The most important component in LBP is strength training exercises and one spinal stability with back strengthening exercises and core stability exercise. The purpose of this study to determine that core stability training exercise is better than a back strengthening exercise in increasing the functional activity of the batik craftsmen with low back pain in Pekalongan. The research designs is experiment true by the one group pre-test and post-test group design, conducted in January to August 2014. Samples were taken by purposive sampling with inclusion and exclusion criteria. In this study consist of 28 people with batik craftsmen low back pain who have worked a minimum of 5-20 years. Subjects were divided into two groups: group 1 (were given training back strengthening exercises) and group 2 (were given training core stability exercise). Measurement instruments to assess the functional activity used the Pain Disability Index (PDI). The result of statistical test with paired t-test found that the reduction in PDI scores of group 1 with p value = 0.001 and data reduction PDI score group 2 p value = 0.001. Different of PDI scores after treatment were analisys by Independent t-test in 2 groups with p value = 0.001 (p